Smart Pricing, Winning Promotions, and Market Share: The Triple Formula for MSME Profitability - Ridwan, Muhammad; Mulyani, Sitti Rizki; Putra, Rio Andhika; Kodri, Aida Nur Mohd; Kumbara, Vicky Brama (GOVERNORS, 2025)
This study investigates the influence of pricing strategy, promotion, and market share on the profitability of Micro, Small, and Medium Enterprises (MSMEs) in Padang City. Using primary data collected through questionnaire surveys and a quota sampling technique, 100 valid responses were analyzed via multiple regression analysis using SPSS. Using multiple regression analysis, the findings show that both pricing and promotional strategies have a positive and significant effect on MSME profitability. Competitive pricing based on production costs and attractive promotions such as discounts and social media campaigns contribute to increased sales and brand recognition. However, market share does not have a significant effect on profitability, likely due to competition intensity, limited resources, and inefficient operations. Based on these results, MSMEs are encouraged to apply flexible pricing strategies, strengthen promotional efforts, and improve operational efficiency. Support from the government and stakeholders through training, digital marketing assistance, and improved access to capital is also recommended. The study is limited by its focus on Padang City, a relatively small sample size, and limited variables. Future research should consider broader geographic coverage, larger samples, additional influencing factors like product quality and external conditions, and the use of mixed methods and longitudinal designs. This research offers valuable insights for improving MSME profitability and serves as a reference for strategic development efforts in similar business environments.